Association of the number of sentinel lymph nodes harvested with survival in breast cancer. Issue 1 (January 2015) - Bonneau, C.; Bendifallah, S.; Reyal, F.; Rossi, L.; Rouzier, R.
Abstract Aims In patients with breast cancer, the association between the number of sentinel lymph node (SLN) removed and survival is poorly known. Our objective was to evaluate this association on disease-specific survival (DSS). Methods Data of 144 517 patients with invasive T1-3M0 breast carcinoma and initial treatment with SLN biopsy were extracted from the SEER database. Univariate and multivariate analyses were performed. Results The number of SLNs harvested and the completion of axillary lymph node dissection (ALND) were not associated with DSS improvement for patients without metastatic nodes. After adjustment, patients with three SLNs had a better DSS than did other groups (HR of 0.73 CI 95% [0.60–0.88], p = 0.001). This result was mainly driven by the group of patients with one metastatic LN. When patients had two or more metastatic LNs, there was no difference in DSS according to the number of SLNs or to completion of ALND. Conclusions The number of SLN harvested was associated with DSS. According to DSS, the optimal number of SLNs harvested was three in this large series, thereby calling into question the understaging or undertreatment of SLN biopsy in which only one or two SLNs are harvested but also the therapeutic effect of completion ALND.